High-power subnanosecond 38-GHz microwave pulses generated at a repetition rate of up to 3.5 kHz - Grishin D. M.; Gubanov V. P.; Korovin S. D.; Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Nikiforov A. V.; Rostov V. V.; Rukin S. N.; Slovikovskii B. G.; Ul'maskulov M. R.; Sharypov K. A.; Shpak V. G.; et al. (2002, 2002)
Title screen